Personal Resources for Psychological Well-Being in University Students: The Roles of Psychological Capital and Coping Strategies - Esteban Moreno-Montero; María del Mar Ferradás; Carlos Freire (MDPI AG, 2024)
In recent years, research has noted the increasing prevalence of mental health problems among university students. The current mental health needs of the university population, along with the multitude of stressors they face, have increased the importance of examining their psychological well-being and determining the personal resources that effectively promote it. In this context, the present research aims to analyze the roles of psychological capital (PsyCap) and coping strategies as personal resources that are significantly related to the psychological well-being (PWB) of university students. Specifically, the mediating roles of various coping strategies (both adaptive and maladaptive) in the relationship between PsyCap and PWB are explored. The study involves 391 university students from Spain. The results show partial mediation effects of adaptive coping strategies (cognitive restructuring and social support) on the relationship between PsyCap and PWB. Likewise, PsyCap is shown to be a direct positive predictor of adaptive coping strategies and PWB, as well as a direct negative predictor of maladaptive coping strategies (self-criticism). Therefore, it is concluded that PsyCap and some adaptive coping strategies serve as valuable personal resources that predict PWB in university students. PsyCap is also associated with a lower tendency to engage in maladaptive coping strategies, such as self-criticism. Similarly, the use of cognitive restructuring and/or social support is related to high levels of PWB among university students.